Morphometric Characterization of Minahasa Horse for Breeding and Conservation Purposes - B J Takaendengan; R R Noor; S Adiani (Faculty of Animal Science, Bogor Agricultural University, 2011)
The objective of this study was to investigate morphometric variation of Minahasa horses. Body measurements and live-weight were taken on 195 mare and 310 stallion of Minahasa horse. A multivariate approach was adopted to provide description of both body shape and body size of four Minahasa local horse populations, i.e. Tomohon, Manado, South Minahasa, and Minahasa. Statistical methods employed in this study were general linear model, simple discriminant analysis, and principle component analysis were used to construct phylogenic trees. The results showed that Tomohon’s horse population had higher body weights and body measurements (P<0.05) than those from three other areas (Manado, South Minahasa, and Minahasa). The hip width is the most discriminant variable to determine the differences among Minahasa local horse population. The results support establishment of strategy to promote the use and the development of local adapted horse.